Petroleum Hydrocarbon along the Coastal Areas of Port Dickson - Law, A. T.; Veellu, Ravinthar (1989)
The petroleum hydrocarbon content in water and sand along the coast of Port Dickson was studied between December 1984 and November 1985. The mean and range of petroleum hydrocarbon in water were 32.24 ppb and 2.52-73.34 ppb respectively, while for the sand, the range was between 2.1 and 70.4 mg/kg d1)1 sand. A pronounced fluctuation of hydrocarbon level in water with sampling date was detected at the sampling stations during the sampling period. The results indicated that the coastal area of Port Dickson carried some degree of hydrocarbon pollution.